Customer Continuance Intention Toward the Use of Electronic Money - Candy, Candy; Budiman, Johny; Wijaya, Chandra; Ernestine, Ernestine; Mayviana, Vivin (Jurnal Ilmu Manajemen Advantage, 2025)
The rapid development of financial technology has transformed the way people conduct financial transactions, including the use of electronic money (e-money). However, despite this growth, many users discontinue using e-money over time, highlighting a gap in understanding the factors that sustain its usage. Various factors, such as customer innovativeness, ease of use, and perceived security, influence the adoption of e-money services. This study addresses this problem by identifying the influence of customer innovativeness, perceived behavioral control (PBC), and e-security on customer continuance intention to e-money usage (CCIEU). The study uses a descriptive method and a quantitative approach. Data was gathered through an online survey, where e-money users filled out questionnaires. The analysis was done using the PLS-SEM (Partial Least Squares Structural Equation Modeling) technique. The findings show that customer innovativeness has a positive impact on CCIEU, mediated by PBC. However, e-security does not have a strong effect on between the relationship between customer innovativeness and CCIEU. These findings provide useful insights for formulating strategies to enhance e-money adoption in society.